Writing and learning with computers - Dowling, Carolyn (Camberwell, Vic. : Australian Council for Educational Research, 1999)
This book is about: Word processing and the writing process; Word processing in the classroom; Hypertext in theory and practice; Multimedia and writing; Multimedia in the classroom; ...
Keywords: English language; English writing; English language -- Writing; Computers; Authorship -- Data processing